Using simio to automatically create 3d warehouses and compare different storage strategies - Vieira, António Amaro Costa (2015)
This paper focuses on a simulation based approach to reduce warehouse costs. At an early stage, the tool needs to be able to generate different types of warehouses. To accomplish this, a Simio add-in was built in C#, using the Simio API, where the user only needs to insert the layout data on an excel spreadsheet. Afterwards, the created warehouse is capable of modelling different storage strategies and compare them. The obtained results indicate that the proposed strategy is able to reduce the picking time in about 15% and the number of stops per milk run in 50%. Moreover, it was found that the strategy currently in use needs 35% more space than the proposed one.